Differences in embryo quality are associated with differences in oocyte composition: A proteomic study in inbred mice. Issue 4 (3rd January 2015) - Pfeiffer, Martin J.; Taher, Leila; Drexler, Hannes; Suzuki, Yutaka; Makałowski, Wojciech; Schwarzer, Caroline; Wang, Bingyuan; Fuellen, Georg; Boiani, Michele; Krijgsveld, Jeroen
<x xml:space="preserve">Abstract</x> Current models of early mouse development assign roles to stochastic processes and epigenetic regulation, which are considered to be as influential as the genetic differences that exist between strains of the species Mus musculus. The aim of this study was to test whether mouse oocytes vary from each other in the abundance of gene products that could influence, prime, or even predetermine developmental trajectories and features of derivative embryos. Using the paradigm of inbred mouse strains, we quantified 2010 protein groups (SILAC LC‐MS/MS) and 15205 transcripts (RNA deep sequencing) present simultaneously in oocytes of four strains tested (129/Sv, C57Bl/6J, C3H/HeN, DBA/2J). Oocytes differed according to donor strain in the abundance of catalytic and regulatory proteins, as confirmed for a subset (bromodomain adjacent to zinc finger domain, 1B [BAZ1B], heme oxygenase 1 [HMOX1], estrogen related receptor, beta [ESRRB]) via immunofluorescence in situ. Given a Pearson's r correlation coefficient of 0.18–0.20, the abundance of oocytic proteins could not be predicted from that of cognate mRNAs. Our results document that a prerequisite to generate embryo diversity, namely the different abundances of maternal proteins in oocytes, can be studied in the model of inbred mouse strains. Thus, we highlight the importance of proteomic quantifications in modern embryology. All MS data have been deposited in the ProteomeXchange with identifier PXD001059 (http://proteomecentral.proteomexchange.org/dataset/PXD001059).